Perusal of the Finite Element Method - Petrova, Radostina (IntechOpen, 2016)
The finite element method (FEM) is a numerical technique for finding approximate solutions to different numerical problems. The practical applications of FEM are known as finite element analysis (FEA). FEA is a good choice for analyzing problems over complicated domains. The first three chapters of this book contribute to the development of new FE techniques by examining a few key hurdles of the FEM and proposing techniques to mitigate them. The next four chapters focus on the close connection between the development of a new technique and its implementation. Current state-of-the-art software packages for FEA allow the construction, refinement, and optimization of entire designs before manufacturing. This is convincingly demonstrated in the last three chapters of the book with examples from the field of biomechanical engineering. This book presents a current research by highlighting the vitality and potential of the finite elements for the future development of more efficient numerical techniques, new areas of application, and FEA's important role in practical engineering.